Contextualising the Neolithic Occupation of Southern Vietnam - Sarjeant, Carmen (Terra Australis, 2014)
Excavated in 2009, An Son, Long An Province, southern Vietnam has been dated to the second millennium BC, with evidence for neolithic occupation and burials. Very little is known about the neolithic period in southern Vietnam, and the routes and chronology for the appearance of cultivation, domestic animals, and ceramic and lithic technologies associated with sedentary settlements in mainland Southeast Asia are still debated.